Material ratio curve of 3D surface topography of additively manufactured parts: an attempt to characterise open surface pores. (18th March 2021) - Lou, S; Zhu, Z; Zeng, W; Majewski, C; Scott, P J; Jiang, X
Abstract: Surface topography of additively manufactured components often contains 3D features, e.g. particles, open surface pores. X-ray computed topography can capture these features, allowing measurement data to be used for 3D surface texture characterisation. On the basis of the newly developed 3D surface texture parameters, this paper investigates material ratio curves of the surfaces produced by additive manufacturing processes, i.e. selective laser melting and high speed sintering. The material ratio curves of these surfaces vary in their shapes, depending on the specific process and associated process parameters, as well as surface orientations. Re-entrant topography features can result in recess shapes on the material ratio curve at the surface heights where these features locate. This unique characteristic makes the material ratio curve an effective analysis tool to differentiate various AM surface topographies, allowing surface texture to be linked with process control and functional assessment. Furthermore, V v v (valley void volume) is identified as a useful volume parameter to characterise the open surface pores of AM surfaces. The material ratio M r 2 for the determination of V v v is discussed with the consideration of three options to address the open surface pores. The secant scanning approach proposed by ISO 13565-2 and the manual set ratio at the first sharp drop of the material ratio curve were found to be able to achieve reasonable results for the AM open surface pore characterisation.